2021
DOI: 10.1073/pnas.2100920118
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell sequencing reveals suppressive transcriptional programs regulated by MIS/AMH in neonatal ovaries

Abstract: Müllerian inhibiting substance (MIS/AMH), produced by granulosa cells of growing follicles, is an important regulator of folliculogenesis and follicle development. Treatment with exogenous MIS in mice suppresses follicle development and prevents ovulation. To investigate the mechanisms by which MIS inhibits follicle development, we performed single-cell RNA sequencing of whole neonatal ovaries treated with MIS at birth and analyzed at postnatal day 6, coinciding with the first wave of follicle growth. We ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
51
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 54 publications
5
51
0
Order By: Relevance
“…However, data about ovarian stromal cells remain elusive and comparatively scarce in previous studies. Recent scRNA data from mice and humans have shown heterogeneity of ovarian stromal cells, but these studies mainly focused on GCs and oocytes [16][17][18][19][20][21] . Single-cell sequencing fails to provide spatial information of cell populations, which leads to incomplete characterization of ovarian stromal cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, data about ovarian stromal cells remain elusive and comparatively scarce in previous studies. Recent scRNA data from mice and humans have shown heterogeneity of ovarian stromal cells, but these studies mainly focused on GCs and oocytes [16][17][18][19][20][21] . Single-cell sequencing fails to provide spatial information of cell populations, which leads to incomplete characterization of ovarian stromal cells.…”
Section: Discussionmentioning
confidence: 99%
“…3E ). Meinsohn et al ( 52 ) showed that administration of AMH suppresses follicle development and ovulation and used scRNA-seq to demonstrate that increased activity of AP1 transcription factors coincides with this phenotype; our observation that FOS, FOSB, JUN, and JUNB are decreased may suggest that modulation of these immediate early genes underlies a switch from inhibition of follicle growth to differentiation of GCs in antral follicles.…”
Section: Discussionmentioning
confidence: 57%
“…These differences between preantral and antral follicle mural granulosa cells were reflected in pseudotime trajectory analysis, suggesting that the preantral granulosa cell states are conserved in the cumulus cells of antral follicles while the mural granulosa cells of antral follicles are further differentiated and form a separate branch in the pseudotime trajectory. An example of shared marker expression between preantral and cumulus granulosa is Kctd14, a member of the Potassium Channel Tetramerisation Domain Containing family in granulosa cells expressed during the initial growth of early pre-antral follicles, which we had previously shown to be regulated by AMH (Meinsohn et al, 2021). RNAscope analysis of Kctd14 expression identified a group of cells present in preantral follicles directly adjacent to the oocyte that were destined to differentiate into cumulus cells of large antral follicles.…”
Section: Discussionmentioning
confidence: 99%
“…Single cell RNA sequencing has been used in a variety of tissues to obtain an in-depth understanding of gene expression and cellular diversity. In the ovary, this technique has allowed us and others to explore various physiologic processes during early ovarian development and ovarian aging (Zhao et al 2020; Stévant et al 2019; Wagner et al 2020; Niu and Spradling 2020; Jevitt et al 2020; Man et al 2020; Meinsohn et al 2021; Fan et al 2019; Si Wang et al 2020). For example, Fan et al catalogued the transcriptomic changes that occur during follicular development and regression and mapped the cell types of the human ovary using surgical specimens (Fan et al 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation